The impact of strategic leadership on the operational strategy and performance of business organisations in South Africa - Serfontein, Jacob Jacobus (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Business Management))--University of Stellenbosch, 2010.